2008
DOI: 10.1007/s10597-008-9137-8
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Social Support for Individuals with Serious Mental Illness: Evaluating the Compeer Model of Intentional Friendship

Abstract: We conducted a quasi-experimental study of Compeer, which matches community volunteers and people with SMI to increase social support. Seventy-five adults with SMI received community psychiatric treatments-usual (TAU) while 79 adults received Compeer services plus TAU. Compeer clients reported significant improvements in social support and a trend towards improved subjective well-being. After 6 months, social support increased >1 SD for 13%, increasing to 23% at 12 months, supporting qualitative research sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
2
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 49 publications
4
60
2
3
Order By: Relevance
“…This result was supported by [25]who highlighted in his study that, typical reasons cited by patients for not taking their medications included forgetfulness (30%), medication cost (22%), other priorities (16%), decision to omit doses (11%), lack of information (9%), and emotional factors (7%) moreover, Increase in patient medication cost share was found to be associated with low adherence to medication [36].According to the Kaiser Family Foundation survey in 2015, approximately three quarters (73%) of the public think the drug prices are unreasonable and blame pharmaceutical companies for setting prices so high. Furthermore, the finding also reflected number of hospitalization is significantly correlated with social support, this result was supported by [37]who highlighted in their study that, persons admitted frequently to mental hospitals or those with prolonged hospitalization have distinctly smaller networks composed for the first time. Also it will be difficult for individuals to reintegrate into community after hospitalization .In the same context, Another study by [30]further found that, people with a larger network, with high level of support located in family and outside the family, have been rarely hospitalized this is incongruent with a study done by [38]who stated that, patients with repeated hospital admissions have networks composed of more mental health and service professionals.…”
Section: Risk Factors Associated With Readmissions Of Hospitalized Mesupporting
confidence: 53%
“…This result was supported by [25]who highlighted in his study that, typical reasons cited by patients for not taking their medications included forgetfulness (30%), medication cost (22%), other priorities (16%), decision to omit doses (11%), lack of information (9%), and emotional factors (7%) moreover, Increase in patient medication cost share was found to be associated with low adherence to medication [36].According to the Kaiser Family Foundation survey in 2015, approximately three quarters (73%) of the public think the drug prices are unreasonable and blame pharmaceutical companies for setting prices so high. Furthermore, the finding also reflected number of hospitalization is significantly correlated with social support, this result was supported by [37]who highlighted in their study that, persons admitted frequently to mental hospitals or those with prolonged hospitalization have distinctly smaller networks composed for the first time. Also it will be difficult for individuals to reintegrate into community after hospitalization .In the same context, Another study by [30]further found that, people with a larger network, with high level of support located in family and outside the family, have been rarely hospitalized this is incongruent with a study done by [38]who stated that, patients with repeated hospital admissions have networks composed of more mental health and service professionals.…”
Section: Risk Factors Associated With Readmissions Of Hospitalized Mesupporting
confidence: 53%
“…Women who were connected to families and other social supports voiced fewer concerns about social isolation, a finding that reinforces the value of family and social supports as a potential buffer to loneliness and isolation (McCorkle et al 2008;Perese and Wolf 2005;Evert et al 2003;Corrigan and Phelan 2004). The importance of having personal relationships and social supports may differ between women and men.…”
Section: Discussionmentioning
confidence: 93%
“…Rhesus monkeys contain a polymorphism in the serotonin transporter gene (Barr et al, 2004c), which is homologous to the serotonin transporter polymorphism in humans and affects bioavailability of serotonin. Infant and juvenile rhesus monkeys that were homozygous for the short form of the (s) allele in the promoter region of the 5-hydroxytryptamine (5-HT) transporter gene (5HTTLPR) were found to consistently show a pattern of anxiety and inhibition in a battery of emotional tests (Bethea et al, 2004;McCorkle et al, 2008). Likewise, cynomolgus monkeys who were categorized as being more stress reactive by ceasing to ovulate in response to mild stressors displayed hypofunctioning of the serotonergic system in response to a pharmacological challenge (Bethea et al, 2005).…”
Section: Adverse Rearing Interacts With Genotypementioning
confidence: 99%
“…Most non-human primate species live in complex social environments, which require sophisticated social cognition and behavior to recruit social support, alliance formation, and recognition of emotional displays (see for example, Maestripieri, 2007). Many psychiatric diseases are defined by their interference with normal social interactions, associated with impaired social and cognitive skills, and are in turn exacerbated when social support is inadequate or unreliable (Lam and Rosenheck, 1999;McCorkle et al, 2008;McManus, 1996).…”
Section: Introductionmentioning
confidence: 99%